AIDS legislation--turning up the heat? - Kirby, M. D. (Journal of medical ethics, 1986)
This paper is not about the medical condition of AIDS. Nor is it about the history of the condition since it was first reported in Atlanta, Georgia in 1981. It looks rather, at the catalogue of legislative and other legal responses to the spread of AIDS. The paper analyses the AIDS condition in its historical context. The hysteria accompanying the outbreak of AIDS is contrasted with the similar hysteria associated with other previous epidemics experienced in Australia over the past two centuries. The paper categorises the responses of lawmakers to the condition, according to the approach taken; from 'full blast', through 'moderate heat' to 'low key' or an attempt to avoid or minimise legal intervention. It is suggested that the appropriate response should depend upon such factors as the present magnitude of the condition, its likely future course, the availability of cures and protections against its spread and objectives being sought by intervention. Unless these factors are taken into account gross over-reaction can occur, causing social disruption and much personal injustice.